Organizing, Operating, and Terminating Subchapter S Corporations. - Yohe, D. Spencer; Sterling, Robert R. (The Accounting Review, 1971)
Reviews the book "Organizing, Operating, and Terminating Subchapter S Corporations," by D. Larry Crumbley and P. Michael Davis.